The Thermal Protective Performance of Firefighters' Clothing: The Air Gap Between the Clothing and the Body. Issue 10 (3rd July 2017) - Ghazy, Ahmed
ABSTRACT: The air gaps entrapped in firefighters' clothing play a crucial role in determining the protective performance of the clothing. Nevertheless, most of the models in the literature ignored the air gaps between the clothing layers and dealt with the air gap between the clothing and the body in an approximate way. In addition, none of these studies addressed the influence of these air gaps on the protective performance of the clothing. This paper introduces a finite-volume model that employs a more realistic analysis for the air gaps entrapped in firefighters' clothing as compared to the typical model in the literature. The paper further investigates the influence of different clothing parameters on the heat release from the clothing to the skin and their corresponding influence on the clothing protective performance. Skin burns predictions made by the present model were compared to those made by the typical model in the literature. The paper demonstrates the influence of the air gap between firefighters' protective clothing and the body on the protection provided by the clothing. The paper also illustrates that inappropriate modeling of the air gaps entrapped in firefighters' clothing would underestimate the protective performance of the clothing.